2020
DOI: 10.3390/polym12030666
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polyol/Crosslinker Blend Composition on Phase Separation and Thermo-Mechanical Properties of Polyurethane Thin Films

Abstract: Polyurethanes (PUs) from Polyethylene glycol (PEG) and polycaprolactone diol (PCL) and a crosslinker, Pentaerythritol (PE), were synthetized with isophorone diisocyanate (IPDI). In this study, we investigated the effect of polyol and crosslinker composition on phase separation and thermo-mechanical properties. The properties were studied through dynamic mechanical analysis, X-ray scattering, atomic force microscopy (AFM), and thermogravimetric analysis (TGA). The results showed changes in PUs properties, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 27 publications
(39 reference statements)
3
32
0
Order By: Relevance
“…That crystallinity decreased with the amount of PCL in the polyurethane owing to the semi-crystalline nature of PCL as well as the amount of PEG and crosslinking agent used. This information complements the previous investigation of the research group 21 , in which it was observed that at a lower average molecular weight of polyols, the DOI: 10.1557/jmr.2020.303 crystallinity of the biomaterial may decrease at low temperatures and a decrease in the crosslinking agent will decrease the PEG/PCL/PE polyurethane phase mixing 21 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…That crystallinity decreased with the amount of PCL in the polyurethane owing to the semi-crystalline nature of PCL as well as the amount of PEG and crosslinking agent used. This information complements the previous investigation of the research group 21 , in which it was observed that at a lower average molecular weight of polyols, the DOI: 10.1557/jmr.2020.303 crystallinity of the biomaterial may decrease at low temperatures and a decrease in the crosslinking agent will decrease the PEG/PCL/PE polyurethane phase mixing 21 .…”
Section: Resultssupporting
confidence: 86%
“…Polyurethanes were synthetised via a two-step polymerisation 21 . PCL and PEG were used as polyols, isophorone diisocyanate as an NCO source, and pentaerythritol as a crosslinker.…”
Section: Polyurethane Synthesismentioning
confidence: 99%
“…We have previously reported on the thermomechanical characterization of the polyurethanes studied here [21]. Dynamic-mechanical-thermal analysis revealed a typical elastomeric behavior and the glass transition temperature ranged from −44 to −37 °C.…”
Section: Introductionmentioning
confidence: 88%
“…However, the ultimate strength values were similar across all of the compositions, with nonsignificant differences. As described in our previous work [21] [43,44]. Such softening, mediated by water absorption, could provide advantages for medical applications [14].…”
Section: Mechanical Assessmentmentioning
confidence: 99%
“…Some works have been devoted to the influence of crosslinker on properties of PU. For example, Arévalo-Alquichire et al [ 22 ] synthesized a PU using pentaerythritol as a crosslinker. Results indicated that the largest concentration of cross-linkers produced more distributed segment segregation and higher thermal stability.…”
Section: Introductionmentioning
confidence: 99%